Dinamika Pemikiran Islam di Indonesia Kontemporer - Puad Hasan; Zaenal Abidin (STIT Sirojul Falah Bogor, 2024)
ABSTRACT This article attempts to explore the dynamics of Islamic intellectualism and thought in Indonesia by examining its characteristics, origins, development, actors and struggles. In this context, Islamic thought in Indonesia is understood as a stage in which the understanding and practice of Islam established in the Nusantara is revisited, criticized, deepened and